2020
DOI: 10.1093/humrep/deaa303
|View full text |Cite
|
Sign up to set email alerts
|

Something old, something new: digital quantification of uterine vascular remodelling and trophoblast plugging in historical collections provides new insight into adaptation of the utero-placental circulation

Abstract: STUDY QUESTION What is the physiological extent of vascular remodelling in and trophoblast plugging of the uterine circulation across the first half of pregnancy? SUMMARY ANSWER All levels of the uterine vascular tree (arcuate, radial and spiral arteries (SAs)) dilate ∼2.6- to 4.3-fold between 6 and 20 weeks of gestation, with significant aggregates of trophoblasts persisting in the decidual and myometrial parts of SAs beyond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 43 publications
1
44
0
Order By: Relevance
“…Furthermore, if UtA flow is directly dependent on SpA flow then there should be a linear relationship between flow and the progressive canalization of the SpA trophoblast plugs; this has not been observed [23]. Instead, there is a significant increase in flux at 13 weeks, currently attributed to increases in radial artery lumen diameters [23,24].…”
Section: Uterine Artery Doppler Waveformmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, if UtA flow is directly dependent on SpA flow then there should be a linear relationship between flow and the progressive canalization of the SpA trophoblast plugs; this has not been observed [23]. Instead, there is a significant increase in flux at 13 weeks, currently attributed to increases in radial artery lumen diameters [23,24].…”
Section: Uterine Artery Doppler Waveformmentioning
confidence: 99%
“…Consequently, radial artery remodelling may be key to understanding changes in early second trimester uteroplacental flow and resistance, and hence the UtA waveform [23]. Recently, Allerkamp et al recorded that the junctional SpAs dilated last, after retrograde remodelling of the other vessels, proposing the rapid increase in blood flow into the IVS may be due to increases in SpA dimensions as well as radial artery dimensions [24]. However, as many of these studies have been based on ex vivo specimens it is difficult to confirm the precise timeline of the changes and further investigation is required.…”
Section: Uterine Artery Doppler Waveformmentioning
confidence: 99%
“…However, recent findings suggest that trophoblast plug disintegration is not completed by the end of the first trimester, but immunohistochemical staining indicated a partial persistence until mid-gestation. The rapid increase in blood flow into the IVS that was observed by end of first trimester can, however, be traced back to a dimensional increase of the arteries [ 43 ].…”
Section: Interaction Of Maternal Platelets and Trophoblastsmentioning
confidence: 99%
“…Towards the end of the first trimester, the endovascular aggregates canalise, which, along with coordinated remodelling of the arcuate and radial arteries ( Allerkamp et al, 2020 ), allows full onset of the maternal circulation as confirmed by a threefold rise in the intraplacental oxygen concentration ( Jauniaux et al, 2000 ). The rise is thought to induce maturational changes, including villous regression to form the definitive placenta and the membranes ( Jauniaux et al, 2003b ).…”
Section: Introductionmentioning
confidence: 99%